The Procedural System of Civil Liability for Disseminating Rumors on Social Media - Jaber, Mohammed Dhahir; Shobeiri , Seyed Hassan (Journal of Ecohumanism, 2024)
The rapid advancements in technology have transformed various aspects of life, with social media platforms emerging as a significant outcome of this shift. These platforms have revolutionized global communication among individuals and organizations but have also introduced challenges, particularly in relation to privacy, as users increasingly share personal data or are required to provide such data for registration. This study explores the procedural civil liability associated with the dissemination of rumors on social media, a phenomenon that has become a tool for states to secure their interests in various fields. Through a comparative analytical methodology, the research examines the concept of contractual liability in the context of social media, identifying three primary relationships that can give rise to such liability: between platforms and developers or publishers under employment contracts, between users and platforms through terms of service agreements, and between users themselves via contracts like advertising agreements. The study concludes that when a valid contract is breached, contractual liability is established. It underscores the need for judicial mechanisms to address Rumor-related offenses, recommending the creation of specialized chambers within general and appellate courts to manage such cases. Furthermore, it emphasizes the role of the Supreme Judicial Council in establishing these specialized judicial bodies to address emerging legal challenges beyond the scope of existing legal frameworks.